Epigenetics Modulators as Therapeutics for Neurological Disorders - Gaba, Mansi; Sharma, Ashwani; Chitranshi, Nitin; Kumar, Girish; Virmani, Reshu; Virmani, Tarun; Gugulothu, Dalapathi (Current Pharmaceutical Design, 2025)
Epigenetics mechanisms play a crucial role in regulating gene expression and cellular function in the development and progression of neurological disorders. Emerging evidence suggests that dysregulation of these epigenetic processes contributes significantly to the pathogenesis of various neurological disorders, including Alzheimer's disease, Parkinson's disease, and epilepsy. Epigenetic mechanisms, including DNA methylation, histone modification, and non-coding RNAs, significantly impact neural plasticity. The use of epigenetic modulators, including DNA methyltransferase and histone deacetylase inhibitors, offers a promising strategy to correct and modify aberrant epigenetic marks, potentially restoring neurological homeostasis. This review highlights recent research findings from ongoing clinical trials and the potential benefits and challenges of epigenetic therapies for neurological disorders. We discuss the capacity of these interventions to potentially halt or reverse disease progression, their targeted nature, and their neuroprotective effects. Additionally, we address the hurdles facing the field, including issues of specificity, delivery, and long-term efficacy.
Keywords: DNA methylation